2016
DOI: 10.3892/ol.2016.4666
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of papillary thyroid cancer stem cells to chemotherapy

Abstract: Abstract. Thyroid carcinoma is the most common endocrine neoplasm, with the highest mortality rate of all the endocrine cancers. Among the endocrine malignancies, ~80% are papillary thyroid carcinomas (PTCs). In the initiation and progression of this tumor, genetic alterations in the mitogen-associated protein kinase pathway, including RAS point mutations, RET/PTC oncogene rearrangements and BRAF point mutations, play an important role, particularly in deciding targeted therapy. In the present study, a small p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…The incidence of thyroid cancer is continuing to increase worldwide (20). Compared with males, females of various ethnicities demonstrate a higher incidence of thyroid cancer (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of thyroid cancer is continuing to increase worldwide (20). Compared with males, females of various ethnicities demonstrate a higher incidence of thyroid cancer (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it is common for these patients to develop drug resistance (23,24). Most thyroid cancer patients who develop incurable metastasis are candidates for neoadjuvant or palliative chemotherapy (20,25). However, two thirds of these patients still benefit from conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further in clinical studies, stem cell markers have been found upregulated in PTC tissues, and the expression levels of these markers were positively correlated with lymph node, tumors metastasis stage . For treatment, one study suggested that PTC was more resistant to bortezomib, taxol, cisplatin, etoposide, and other chemotherapeutics drugs . In addition, another study reported that the expression of CD15, CD44, CD166, and ALDH1 was positively independently correlated with a shorter progression‐free survival (PFS) .…”
Section: Introductionmentioning
confidence: 99%
“…of cancer therapy (27). Therefore, increased understanding of the characteristics of thyroid CSCs and the identification of therapeutic agents that target the CSC population may lead to the development of novel treatments that specifically target ATC and advanced forms of differentiated tumors.…”
Section: Cancer Stem Cells As a Potential Therapeutic Target In Thyromentioning
confidence: 99%